Identification of Genes in Positive Alleles Marking Type 2 Diabetes Mellitus Using Primer A18: Identifikasi Gen pada Alel Positif Penanda Diabetes Melitus Tipe 2 Menggunakan Primer A18 - Firda, Aminatul; Mushlih, Miftahul (Indonesian Journal of Innovation Studies, 2021)
Diabetes mellitus type 2 (DMT2) is a disorder characterized by hyperglycemia due to impaired insulin secretion and insulin resistance. The purpose of this study was to identify the gene involved in the positive allele of DMT2 marker using A18 primer and is a type of exploratory descriptive study. The samples used were 2 samples of DMT2 patients from the villages of Taman and Balongbend, and 8 samples of DNA collection at the Molecular Biology Laboratory, Muhammadiyah University of Sidoarj. Based on the genetic analysis carried out, the GATB gene (Glutamyl-tRNA Amidotransferase Sub Unit B) was identified in the positive allele with a homology value of "percentage identity" between the sample sequence and the sequence data in the NCBI Genbank of 80 and 88%. This research hypothesizes that the GATB gene has a relationship with the emergence of DMT2 as evidenced by the relationship between the gene and the performance of mitochondria to produce ATP which is needed by pancreatic beta cells to produce insulin.